Development of Virtual Media Nata De Pina Based on Articulate Storyline to Improve Science Process Skills (SPS) of Grade IX Students in Biotechnology Material - Resi Mandalia; Elsje Theodora Maasawet; Daniel Tarigan; Abdul Hakim; Yusak Hudiyono; Lambang Subagiyo; Masitah; Herliani; Krishna Purnawan Candra (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to evaluate the feasibility, practicality and impact of the implementation of interactive learning media based on Articulate Storyline in the Conventional Biotechnology sub-material on the science process skills (SPS) of grade IX junior high school students. The research model used is the development of ADDIE with a quasi-experimental approach, pretest-posttest control group design. The subjects of the study consisted of 71 students divided into two classes; experimental class and control class. The results of data analysis showed that there was a significant increase in science process skills (SPS) using Articulate storyline-based media compared to the control class. The developed Articulate storyline-based media was feasible and practical to apply with an average score of 88.79 based on the assessment of material experts and media experts. The students' response to the media reached an average of 90.49 with a very good category. In the experimental class, it showed an increase in science process skills (SPS) with an N-gain value of 0.61 which was categorized as a moderate increase, with an average pretest value of 42.50 increasing to 77.08 in the posttest. These findings indicate that interactive learning media based on Articulate Storyline is effective in improving students' science process skills (SPS) and is recommended for application to other science materials.